Metabolic Signaling and Spatial Interactions in the Oral Polymicrobial Community. (November 2019) - Miller, D.P.; Fitzsimonds, Z.R.; Lamont, R.J.
Oral supra- and subgingival biofilms are complex communities in which hundreds of bacteria, viruses, and fungi reside and interact. In these social environments, microbes compete and cooperate for resources, such as living space and nutrients. The metabolic activities of bacteria can transform their microenvironment and dynamically influence the fitness and growth of cohabitating organisms. Biofilm communities are temporally and spatially organized largely due to cell-to-cell communication, which promotes synergistic interactions. Metabolic interactions maintain biofilm homeostasis through mutualistic cross-feeding, metabolic syntrophy, and cross-respiration. These interactions include reciprocal metabolite exchanges that promote the growth of physiologically compatible bacteria, processive catabolism of complex substrates, and unidirectional interactions that are globally important for the polymicrobial community. Additionally, oral bacterial interactions can lead to detoxification of oxidative compounds, which will provide protection to the community at large. It has also been established that specific organisms provide terminal electron acceptors to partner species that result in a shift from fermentation to respiration, thus increasing ATP yields and improving fitness. Indeed, many interspecies relationships are multidimensional, and the net outcome can be spatially and temporally dependent. Cross-kingdom interactions also occur as oral yeast are antagonistic to some oral bacteria, while numerous mutualistic interactions contribute to yeast-bacterial colonization, fitness in the oral community, and the pathogenesis of caries. Consideration of this social environment reveals behaviors and phenotypes that are not apparent through the study of microbes in isolation. Here, we provide a comprehensive overview of the metabolic interactions that shape the oral microbial community.